FACTORS IN THE DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN - Абдужалилова Мадинахон Мухиддин кизи (Galaxy International Interdisciplinary Research Journal, 2023)
The article deals with the concepts of "creativity", "creativity". The author reveals all the components of these concepts, proves the close connection between creativity and creativity, the need to create educational models, programs, technologies for the development of creativity in preschoolers as the most important condition for the development of the life strategy of a creative person.